The impact of a country's economic factors on housing prices: the case of Portugal - Rehman, Saira (2020)
House market is an important sctor not only in the economy of a country, but also for living conditions of the population. This research seeks to understand the main drivers of the house prices of an European country using the Engle-Granger (EG) Cointegration Analysis. Analysing the Portuguese housing market with quartely data between 1998 and 2019 it is possible to show that in long-term unemployment and interest rate are negatively related and that population, inflation and money supply are positively related with house prices.